Longitudinal Associations Between Perfectionistic Strivings, Perfectionistic Concerns, and Sport-Specific Practice in Adolescent Volleyball Players. Issue 3 (June 2020) - Vink, Kristi; Raudsepp, Lennart
This study examined complex longitudinal relationships between perfectionistic strivings, perfectionistic concerns, and sport-specific practice in adolescent volleyball players. We recruited 188 adolescent volleyball players ( M age =15.4, SD = 0.4 years; 113 females, 75 males) to complete measures of perfectionistic strivings and perfectionistic concerns across two competitive seasons and a training diary to assess the quantity and perceived quality of their sport-specific practice. Bivariate latent growth statistical models revealed that, at baseline, higher perfectionistic strivings were associated with a higher quantity and quality of sport-specific practice. Subsequent changes in perfectionistic strivings and dimensions of sport-specific practice were also significantly interrelated. Perfectionistic strivings and perceived quality of sport-specific practice were reciprocally related, while perfectionistic concerns were not related with dimensions of sport-specific practice. An understanding of the causal relationships between these variables will require further research; however, this study demonstrates that perfectionistic strivings may increase adolescent volleyball players' quantity and perceived quality of sport-specific practice.